Enhanced X‐ray diffraction of in vivo‐grown μNS crystals by viscous jets at XFELs. Issue 6 (8th June 2020) - Nagaratnam, Nirupa; Tang, Yanyang; Botha, Sabine; Saul, Justin; Li, Chufeng; Hu, Hao; Zaare, Sahba; Hunter, Mark; Lowry, David; Weierstall, Uwe; Zatsepin, Nadia; Spence, John C. H.; et al.
Abstract : The first SFX diffraction from EGFP‐μNS(448–605) crystals led to initial electron‐density maps that allowed the clear identification of two EGFP molecules as well as of electron density for μNS(448–605) . Determining the crystal structure of μNS using large XFELs in combination with compact light sources will be the first step towards determining the molecular basis of the role of μNS in the early stages of virus morphogenesis. Abstract : μNS is a 70 kDa major nonstructural protein of avian reoviruses, which cause significant economic losses in the poultry industry. They replicate inside viral factories in host cells, and the μNS protein has been suggested to be the minimal viral factor required for factory formation. Thus, determining the structure of μNS is of great importance for understanding its role in viral infection. In the study presented here, a fragment consisting of residues 448–605 of μNS was expressed as an EGFP fusion protein in Sf9 insect cells. EGFP‐μNS(448–605) crystallization in Sf9 cells was monitored and verified by several imaging techniques. Cells infected with the EGFP‐μNS(448–605) baculovirus formed rod‐shaped microcrystals (5–15 µm in length) which were reconstituted in high‐viscosity media (LCP and agarose) and investigated by serial femtosecond X‐ray diffraction using viscous jets at an X‐ray free‐electron laser (XFEL). The crystals diffracted to 4.5 Å resolution. A total of 4227 diffraction snapshots were successfully indexed into a hexagonal lattice with unit‐cell parameters a  = 109.29, b = 110.29, c = 324.97 Å. The final data set was merged and refined to 7.0 Å resolution. Preliminary electron‐density maps were obtained. While more diffraction data are required to solve the structure of μNS(448–605), the current experimental strategy, which couples high‐viscosity crystal delivery at an XFEL with in cellulo crystallization, paves the way towards structure determination of the μNS protein.